Tinjauan Hukum Pidana Islam Terhadap Implementasi Restorative Justice Pada Tindak Pidana Pencurian Buah Kelapa Sawit - Hasibuan, Nur Habibah; Hasibuan, Zulfan Efendi; Sainul, Ahmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study examines the implementation of restorative justice in the crime of theft of palm fruit in Handio village under Islamic criminal law. This type of research is qualitative or field research and the primary data source is data or information obtained directly through interviews with the people of Handio Village, Village Heads/Village Officials, Traditional Leaders, Religious Leaders, Alim Ulama, Hatobangon, Theft perpetrators and Victims. The secondary data sources are books, journals, and documents that are considered related to this paper, while the collection technique is by means of observation, interviews and documentation then the data analysis technique is descriptive qualitative. The results of this study explain that the implementation of Restorative Justice in the crime of theft is a transfer of the formal legal process to non-formal settlement channels to resolve cases peacefully, deliberation, consensus by presenting the parties concerned. Cases peacefully, because the Village Apparatus considers that formally resolving cases will cause problems such as disputes, hostilities and slow down settlement of cases. In this case, it is still categorized as light theft in positive law and Islamic criminal law, if it has not reached the minimum stolen limit, the sanction is Takzir. Resolving cases peacefully can increase solidarity among human beings for a safe and peaceful life. The sanctions imposed on the perpetrators of the crime of theft applied in Handio Village are in the form of fines and making a letter of agreement, if they repeat it they will be processed legally